The association between creativity and 7R polymorphism in the dopamine receptor D4 gene (DRD4) - Mayseless, Naama; Uzefovsky, Florina; Shalev, Idan; Ebstein, Richard P.; Shamay-Tsoory, Simone G. (Frontiers in Human Neuroscience, 2013)
Creativity can be defined as the ability to produce responses that are both novel and appropriate. One way to assess creativity is to measure divergent thinking (DT) abilities that involve generating multiple novel and meaningful responses to open-ended questions. DT abilities have been shown to be associated with dopaminergic activity, and impaired DT has been reported in populations with dopaminergic dysfunctions. Given the strong association between DT and the dopaminergic system, the current study examined a group of healthy individuals (N=185) to determine the role of the repeat polymorphism in exon3 of the DRD4 in creativity. The results show that individuals carrying the DRD4-7R allele scored significantly lower on tests of DT, particularly on the flexibility dimension of DT, compared to non-carriers. The current findings link creative cognition to the dopaminergic system and suggest that dopaminergic dysfunctions in neurological and psychiatric disorders may account for impaired creativity and cognitive flexibility in these individuals.